Prehistory of the Indo-Malaysian Archipelago Revised Edition - Bellwood, Peter (ANU Press, 2007)
Since its publication in 1985, Peter Bellwood's Prehistory of the Indo-Malaysian Archipelago has been hailed as the sole authoritative work on the subject by the leading expert in the field. Now that work has been fully revised and includes a complete up-to-date summary of the archaeology of the region (and relevant neighboring areas of China and Oceania), as well as a comprehensive discussion of new and important issues (such as the "Eve-Garden of Eden" hypothesis and its relevance to the Indo-Malaysian region) and recent advances in macrofamily linguistic classification. Moving north to south from northern Peninsular Malaysia to Timor and west to east from Sumatra to the Moluccas, Bellwood describes human prehistory from initial hominid settlement more than one million years ago to the eve of historical Hindu-Buddhist and Islamic cultures of the region. The archaeological record provides the central focus, but chapters also incorporate essential information from the paleoenvironmental sciences, biological anthropology, linguistics, and social anthropology. Bellwood approaches questions about past cultural and biological developments in the region from a multidisciplinary perspective. Historical issues given extended treatment include the significance of the Homo erectus populations of Java, the dispersal of the present Austronesian-speaking peoples of the region within the past 4,000 years, and the spread of metallurgy since 500 B.C. Bellwood also discusses relationships between the prehistoric populations of the archipelago and those of neighboring regions such as Australia, New Guinea, and mainland Asia.